Long-term survival and causes of death in patients with ST-elevation acute coronary syndrome without obstructive coronary artery disease. (23rd September 2017) - Andersson, Hedvig Bille; Pedersen, Frants; Engstrøm, Thomas; Helqvist, Steffen; Jensen, Morten Kvistholm; Jørgensen, Erik; Kelbæk, Henning; Räder, Sune Bernd Emil Werner; Saunamäki, Kari; Bates, Eric; Grande, Peer; Holmvang, Lene; et al.
Abstract: Aims: We aimed to study survival and causes of death in patients with ST-elevation acute coronary syndrome (STE-ACS) with and without obstructive coronary artery disease (CAD). Methods and results: We included 4793 consecutive patients with STE-ACS triaged for acute coronary angiography at a large cardiac invasive centre (2009–2014). Of these, 88% had obstructive CAD (stenosis ≥50%), 6% had non-obstructive CAD (stenosis 1–49%), and 5% had normal coronary arteries. Patients without obstructive CAD were younger and more often female with fewer cardiovascular risk factors. Median follow-up time was 2.6 years. Compared with patients with obstructive CAD, the short-term hazard of death (≤30 days) was lower in both patients with non-obstructive CAD [hazard ratio (HR) 0.49, 95% confidence interval (CI) 0.27–0.89, P  = 0.018] and normal coronary arteries (HR 0.31, 95% CI 0.11–0.83, P  = 0.021). In contrast, the long-term hazard of death (>30 days) was similar in patients with non-obstructive CAD (HR 1.15, 95% CI 0.77–1.72, P  = 0.487) and higher in patients with normal coronary arteries (HR 2.44, 95% CI 1.58–3.76, P < 0.001), regardless of troponin levels. Causes of death were cardiovascular in 70% of patients with obstructive CAD, 38% with non-obstructive CAD, and 32% with normal coronary arteries. Finally, patients without obstructive CAD had lower survival compared with an age and sex matched general population. Conclusions: STE-ACS patients without obstructive CAD had a long-term risk of death similar to or higher than patients with obstructive CAD. Causes of death were less often cardiovascular. This suggests that STE-ACS patients without obstructive CAD warrant medical attention and close follow-up.